A comparative study of CO2 laser tonsillectomy versus conventional tonsillectomy in our experience - Gandhi, G.; Bhat, Poornima S.; Pradheep, K. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Tonsillectomy is one of the major surgical procedure in terms of volume in the oto-rhino-laryngological practice. It is an age old surgical procedure, referred in history of medicine. There have been various changes in the indications and surgical procedures since 4 to 5 decades. Methods: A comparative study between the CO2 laser and conventional method (dissection Hospital set up, by the same surgeon, using two different techniques. The main objective of the study is to compare the intra-operative events (blood loss, time taken for surgery). This study was done in 40 patients undergoing tonsillectomy with or without adenoid hypertrophy removal over a period of 1 year (June 2015– May 2016). The patients (20 cases) in the first half of this period underwent conventional tonsillectomy whereas the rest (20 cases) underwent CO2 laser tonsillectomy. The gathered data were analysed by SPSS software (Ver-25) and using necessary tests. The differences between studied groups less than 0.5 (p<0.05) considered significant statically. Results: Among 40 patients, 20 cases underwent tonsillectomy by CO2 laser and 20 cases by conventional method. 20 patients who underwent laser tonsillectomy had lesser bleeding (25 ml vs 60 ml) intraoperatively, p<0.05 (significant) and total time consumed during surgery is less (4.5 minutes vs 15 minutes) with laser when compared to conventional method p<0.05 (significant). Conclusions: CO2 laser tonsillectomy is associated with low intraoperative bleeding and less time consuming surgery when compared to conventional tonsillectomy.